SIPUT PROSOBRANCHIA (GASTROPODA, MOLUSKA) PADA RATAAN TERUMBU KARANG DI TELUK MANADO - Jevvrandi E Bambulu; Farnis B Boneka; Billy Th. Wagey (Sam Ratulangi University, 2021)
Molluscs are marine organisms that do not have a backbone, these organisms are associated with coral reefs. This research was conducted with the aim of describing the density and diversity of Prosobranchia snails’ species on coral reef flats. By applying the belt transect method, the results show that the density of the four Mokupa stations has a relatively high density between Tongkeina, Malalayang and Bulo. While for species diversity, Mokupa and Bulo had the highest value than Tongkeina and Malalayang. According to the results of the belt transect method, is the concluded that stations close to people’s homes have the lowest density and species diversity values, this factor is influenced by anthropogenic activities or human activities. Therefore, it is recommended that there be monitoring of snails on coral reefs, especially reef flattening in order to provide information about Prosobranchia snails.Keywords: Prosobranchia, Density, diversity, belt transects, Reef Flats